Interactive learning framework for dynamic simulation and control of two dimensional flexible plate structure - Intan Zaurah Mat Darus, author; Siti Zaiton Mohd. Hashim, author; Mohammad Osman Tokhi, author; International Conference on Intelligent & Advance Systems (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL